The Neuroprotective Effect of Astaxanthin on Pilocarpine-Induced Status Epilepticus in Rats - Deng, Xiaolin; Wang, Ming; Hu, Sihui; Feng, Yonghao; Shao, Yiye; Xie, Yangmei; Wu, Men; Chen, Yinghui; Shi, Xiaohong (Frontiers in Cellular Neuroscience, 2019)
Cognitive dysfunction is one of the serious complications induced by status epilepticus, which has a significant negative impact on patients’ quality of life. Previous studies demonstrated that the pathophysiological changes after SE such as oxidative stress, inflammatory reaction contributes to neuronal damage. A recent study indicated that preventive astaxanthin alleviated epilepsy-induced oxidative stress and neuronal apoptosis in the brain. In the present study, rats were treated with vehicle or astaxanthin (AST) 1 h after SE onset and were injected once every other day for 2 weeks (total of seven times). The results showed that the cognitive function in SE rats was significantly impaired, and AST treatment improved cognitive function in the Morris water maze. Magnetic Resonance Imaging (MRI), hematoxylin-eosin (HE) staining and TdT-mediated dUTP Nick-End Labeling (TUNEL) staining showed obvious damage in the hippocampus of SE rats, and astaxanthin alleviated the damage. Subsequently, we evaluated the effect of astaxanthin on relative pathophysiology to elucidate the possible mechanisms. To evaluate the oxidative stress, the expression of MDA and SOD in plasma were detected using commercially available kits. Nox-4, p22phox, Nrf-2, Ho-1 and sod1 in the parahippocampal cortex and hippocampus were detected using western blot and RT-PCR. The levels of MDA in plasma and Nox-4 and p22phox in the brain - increased in SE rats, and the levels of SOD in plasma and Nrf-2, Ho-1 and sod1 in the brain-decreased. Treatment with AST alleviated these changes. We also detected the levels of inflammatory mediators like cox-2, IL-1β, TNF-α and NF-κB p-p65/p65 in the brain. The inflammatory reaction was significantly activated in the brain of SE rats, and astaxanthin alleviated neuroinflammation. We detected the levels of p-Akt, Akt, Bcl-2, Bax, cleaved caspase-3, and caspase-3 in the parahippocampal cortex and hippocampus using western blot. The levels of p-Akt/Akt and Bcl-2 decreased in SE rats, Bax and cleaved caspase-3/caspase-3 increased, while astaxanthin alleviated these changes. The present study indicated that astaxanthin exerted obvious neuroprotective effect in pilocarpine-induced SE rats.